2018
DOI: 10.1007/s10995-018-2557-3
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Community-Based Oral Health Program for Women and Children at WIC

Abstract: Objectives To evaluate the women, infants, and children (WIC) Oral Health Program in a county in Florida. Methods The non-traditional interdisciplinary program of the current study was designed to reach at-risk populations with untreated dental diseases and limited access to care; it provides oral health education, dental screenings, preventive dental services, and referrals for women, children, and families at WIC offices. We evaluated the health status of patients enrolled in the program and the services pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Xiao et al reported that more than 80% of underserved US pregnant women have at least one untreated decayed tooth, and average number of decayed teeth is 3.9 45 . Similar data indicates that more than 70% of underserved pregnant women in Florida have unmet oral health needs 113 .…”
Section: Are Oral Microorganisms Harbinger For Adverse Birth Outcome?mentioning
confidence: 75%
“…Xiao et al reported that more than 80% of underserved US pregnant women have at least one untreated decayed tooth, and average number of decayed teeth is 3.9 45 . Similar data indicates that more than 70% of underserved pregnant women in Florida have unmet oral health needs 113 .…”
Section: Are Oral Microorganisms Harbinger For Adverse Birth Outcome?mentioning
confidence: 75%
“…Untreated oral diseases among pregnant women with low socioeconomic status have been identified in the other states of the US as well. An interdisciplinary community-based oral health program in Florida US reviewed the dental encounter records of 180 underserved pregnant women in a Women, Infant, Children (WIC) program, and found 71.2% of the pregnant women had unmet dental care needs [47].…”
Section: Discussionmentioning
confidence: 99%
“…Children depend on parents for guidance on basic day to day oral hygiene maintenance. However, while it is helpful for parents to guide children, parents with low level of education, language barriers or lack of time due to their occupation may be unable to provide proper oral health guidance to their children [43]. Practicing healthy behaviors early in life can have a positive impact on children's overall health.…”
Section: Discussionmentioning
confidence: 99%